A Systematic Review of the Public's Knowledge and Understanding of Alzheimer's Disease and Dementia. (July 2015) - Cahill, Suzanne; Pierce, Maria; Werner, Perla; Darley, Andrew; Bobersky, Andrea
Abstract : This paper reports findings from a systematic review of the literature on the general public's knowledge and understanding of dementia/Alzheimer's disease. The key purpose of the review was to evaluate existing literature with specific attention paid to conceptual and methodological issues and to key findings. Over a 20-year period, 40 published articles satisfied the inclusion criteria. Only 4 of these were qualitative and 5 were cross-national. The review revealed a lack of consistency across studies regarding how knowledge was operationalized, approaches to sampling, response rates, and data collection instruments used including validated scales. A consistent finding across the vast majority of studies was the only fair to moderate knowledge and understanding the general public had. The most common misconception was that dementia was a normal part of aging and there was a lack of clarity about at which point normal age-related memory loss problems become severe enough to indicate dementia. Knowledge of dementia was found to be particularly poor among racial and ethnic minority groups where several myths about causes of dementia were found. Findings point to the need for more educational and advocacy programmes on dementia to be developed particularly in low-income to middle-income countries.